Proposta de suporte metodológico para avaliação de maturidade em gerenciamento de projetos em instituições federais de ensino superior - Souza, Daniel Francisco Dumaresq de (2017)
The aim of this work is to develop a methodological support for project management evaluation in Brazilian Federal Universities (IFES). To fulfill this activity successfully, the research was founded on project management maturity models consolidated in the market and scientific literature, and on main critiques listed in this literature. With the objective of developing the methodological support in the form of a maturity model, we have defined seven criteria to compose the model: project management technical capacity, organizational skills, behavioral skills, informatization, resources management, risk management and innovation capability, with five levels of maturity which based a script for semi-structured interview. The responses provided input data to the Multicriteria Decision-Aid ELECTRE TRI. This method allows the flexibilization of classes of model, fitting it to the need of organization through elicitation of weights, thresholds between classes, and pseudo-criteria. The application of the model has occurred in four departments of Federal University of Rio Grande do Norte (UFRN), having in Project Management Secretary of UFRN as partner for eliciting model values. The results show that three departments are within the acceptable standard for university. Although, one of them is about to be reallocated to a lower level of maturity. The fourth department was allocated to the lowest level. The main contributions of the present study are: (1) possibility of flexibilization of the model, according to the organization need, (2) segmented model for IFES, until now not proposed, and (3) a model that takes into account the main critiques to tradicional maturity models.